Dedicated Road Funds : A Preliminary View on a World Bank Initiative - Potter, Barry (IMF Policy Discussion Papers; Policy Discussion Paper, 1997)
In the past, Road Funds have been criticized as inconsistent with effective expenditure control, as distorting the allocation of public sector resources, and as incompatible with efficient management of government resources. This paper considers whether there is a case for a more benevolent view of the new 'second generation' dedicated Road Funds, which have emerged in recent years. The paper concludes that, where a Road Fund pursues a genuine purchasing agency approach, then in principle it can be an efficient means of delivering road maintenance and, perhaps road capital expenditures. But a formidable list of institutional and financial requirements would have to be satisfied for a dedicated Road Fund to be appropriate. These conditions are more likely to be satisfied in developed economies, with efficient budgetary systems already in place. In many developing countries, the better solution may be to reform overall budget institutions, procedures and practices. But if the institutional and financial requirements for an efficient fund can be met, a Road Fund may be appropriate. The question is just how often the right conditions will arise.